Security, risk and trust in e-wallet payment systems: empirical evidence from Indonesia / Machmudin Eka Prasetya and Shuhaida Mohamed Shuhidan - Prasetya, Machmudin Eka; Shuhidan, Shuhaida Mohamed (UiTM Press, 2023)
The growth of e-commerce has created other technological innovations such as online payment initially developed by the banking industry, such as internet banking and mobile banking. However, e-wallet payment innovation has emerged as another online payment option provided by the non-banking sector. Unfortunately, the usage level of e-wallet payment in Indonesia is still considered relatively low compared to the country's internet or even mobile internet usage. This study investigated how perceived risk, trust, and security influence the behavioural intention of e-wallet payment using extended variables commonly used in extended TAM or UTAUT using postgraduate students in universities in Indonesia. The data analysis used Structural Equation Model (SEM) with IBM-AMOS. This study found that perceived trust played a vital role in influencing the behavioural intention of e-wallet payment usage. Perceived trust also acted as a mediator of perceived security in predicting behaviour. The implication of it hopefully will give a direction for e-wallet providers in providing the service to the users and lead more potential users to use it.